2021
DOI: 10.1155/2021/5552226
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of RTA 404 in Human Brain Malignant Glioma Cell Lines via Cell Cycle Arrest via p21/AKT Signaling

Abstract: Background. Glioblastoma multiforme (GBM) is the most common malignant brain tumor in the world. Despite advances in surgical resection, radiotherapy, and chemotherapy, GBM continues to have a poor overall survival. CDDO (2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid), a synthetic triterpenoid, is an Nrf2 activator used to inhibit proliferation and induce differentiation and apoptosis in various cancer cells. One new trifluoroethylamide derivative of CDDO, RTA 404, has been found to have increased ability to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore, these results indicated that incubation with RTA404 inhibited cell viability and initiated cell apoptosis through an intrinsic apoptotic pathway. Although treatment with RTA404 led to cell cycle arrests in previous studies [ 19 ], without significantly change in mitosis index have found in RTA404 treatment. Based on the above results, it seems to imply that RTA404 activated the DNA checkpoint system and induced apoptosis through an intrinsic apoptotic pathway in established U87MG cells.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, these results indicated that incubation with RTA404 inhibited cell viability and initiated cell apoptosis through an intrinsic apoptotic pathway. Although treatment with RTA404 led to cell cycle arrests in previous studies [ 19 ], without significantly change in mitosis index have found in RTA404 treatment. Based on the above results, it seems to imply that RTA404 activated the DNA checkpoint system and induced apoptosis through an intrinsic apoptotic pathway in established U87MG cells.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, in one study, it induced apoptosis in neuroblastoma cells [ 18 ]. In addition, in GMC cells, RTA404 can inhibit proliferation, cell locomotion, and cell cycle progression and induce apoptosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe depletion in S-phase indicates that DNA synthesis is extremely sensitive to RTA 404. However, the author also cannot rule out G2/M block in addition to the S-phase depletion, since cells trapped in the G2/M at the time of treatment by triterpenoids did not progress into G1/G0 phase [14].In the human brain, malignant glioma cell lines incubated with RTA 404 resulted in cell cycle arrest in the G2/M phase [15].As shown in Fig. 5, treatment with RTA 404 led to an increment in the G2/M phase cell population, implying that GBM 8401 cells underwent a delay in the G2/M phase checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…RTA 404 has been found to have neuroprotective effects in some animal models of degenerative diseases, including ischemic stroke [9] and autoimmune encephalomyelitis [11].It has also been found to induce apoptosis of neuroblastoma cells [14]. Furthermore, RTA 404 can inhibit proliferation, cell locomotion, cell cycle progression and induce apoptosis in GBM cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in one study, it induced apoptosis in neuroblastoma cells ( Alabran et al, 2008 ). In addition, in GMC cells, CDDO-TFEA can inhibit proliferation, cell locomotion, and cell cycle progression and induce apoptosis ( Tsai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%